The relationship between crude oil price and money supplies towards stock exchange and stock rice: evidence from Malaysia / Siti Nur Aisya Ahmad Kamal - Ahmad Kamal, Siti Nur Aisya (2017)
This research is conducted to enhance the knowledge about crude oil price, money supplies towards stock price and stock index. It contains a study in which tests the impact of crude oil price, money supplies towards the stock index and stock price. Samples of 30 companies Listed in the Main Board of Bursa Malaysia are selected ranging from the year 1996 to 2016 and will be run by Statistical and Data Analysis Software. The result as can see in the chapter 4, crude oil price and money supply 1 having a positive significant towards stock index but money supply 2 and money supply 3 there is negative significant towards stock index. Meanwhile, crude oil price and money supplies there is no significant towards the stock price.